Metal concentrations in fillet and gill of parrotfish (Scarus ghobban) from the Persian Gulf and implications for human health. (August 2018) - Fakhri, Yadolah; Saha, Narottam; Miri, Ali; Baghaei, Mehdi; Roomiani, Laleh; Ghaderpoori, Mansour; Taghavi, Mahmoud; Keramati, Hassan; Bahmani, Zohreh; Moradi, Bigard; Bay, Abotaleb; Pouya, Rokhsane Hosseini
Abstract: Despite the benefits of seafood's consumption, the bioaccumulation of metals in fish can endanger consumers' health. This study analyzed lead (Pb), mercury (Hg), Arsenic (As), and Cadmium (Cd) concentrations in fillet and gill of parrotfish ( Scarus ghobban ) using flame atomic adsorption spectroscopy (FAAS). The potential non-carcinogenic and carcinogenic health risks due to consumption of Scarus ghobban fillet were assessed by estimating average target hazard quotient (THQ) and total target hazard quotient (TTHQ) and Incremental Lifetime Cancer Risk cancer risk (ILCR) of the analyzed metals. This study indicated that Cd, Pb, As and Hg concentrations were significantly ( p < 0.05) lower than Food and Agriculture Organization (FAO) and national standard limits. The meal concentrations (μg/kg dry weight) in both fillet and gill were ranked as follows Pb > Cd > As > Hg. THQ and TTHQ were lower than 1 for adults and children, indicating that consumers were not at considerable non-carcinogenic risk. However, ILCR value for As was greater than 10 −4, indicating that consumers are at carcinogenic risk. Overall, this research highlighted that although the consumption of parrotfish from the Persian Gulf does not pose non-carcinogenic health risks, carcinogenic risks derived from toxic As can be detrimental for local consumers. Graphical abstract: Highlights: Metals in fillets and gills of parrotfish ( Scarus ghobban ) from Persian Gulf were analyzed. Metal concentrations were significantly lower than FAO and national standard limits. Consumers were not at considerable non-carcinogenic risk. Consumers are at threshold carcinogenic risk.